Pricing and Information Disclosure in Markets with Loss-Averse Consumers - Heiko Karle; Martin Peitz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
Abstract: We develop a theory of imperfect competition with loss-averse consumers. All consumers are fully informed about match value and price at the time they make their purchasing decision. However, a share of consumers are initially uncertain about their tastes and form a reference point consisting of an expected match value and an expected price distribution, while other consumers are perfectly informed all the time. We derive pricing implications in duopoly with asymmetric ?rms. In particular, we show that a market may exhibit more price variation the larger the share of uninformed, loss-averse consumers. We also derive implications for ?rm strategy and public policy concerning ?rms' incentives to inform consumers about their match value prior to forming their reference point.
urn:nbn:de:bvb:19-epub-13242-3
Keywords: 330; Loss Aversion; Reference-Dependent Utility; Information Disclosure; Konsumentenverhalten; Unvollkommene Information; Risikoaversion; Informationsversorgung; Unvollkommener Wettbewerb; Preisdifferenzierung; Preismanagement; Theorie